Ecosystem – What? Public Understanding and Trust in Conservation Science and Ecosystem Services - Thompson, Jessica Leigh; Kaiser, Alina; Sparks, Eric L.; Shelton, Michael; Brunden, Eric; Cherry, Julia A.; Cebrian, Just (Frontiers in Communication, 2016)
In this mixed-methods study, we replicate a national Nature Conservancy survey on a regional scale to understand what local audiences know and believe about ecosystem services and conservation science. After the Deepwater Horizon oil spill in 2010, the Gulf Coast Ecosystem Restoration Council was created and charged with administering a large portion of the $13.7 billion in penalties (via the Gulf Coast Restoration Fund) for ecosystem restoration research and implementation programs. Almost as quickly as oil gushed into the Gulf, conservation organizations (local, state, federal and NGO) along the coast drafted proposals and requests for a piece of the funding. In December 2014, the State of Alabama submitted five proposed restoration projects with an estimated total cost of $54.2 million. Many of the projects use the language of ecosystem science, restoration and services to promote efforts to restore the ecosystem and economy of the Gulf Coast region. These phrases, once disciplinary jargon, are now heard in soundbites on the evening news and seen in the headlines of popular news sources (e.g. AL.com, Gulf Coast News Today, WKRG-Mobile and WPMI-Mobile). As this phraseology becomes more pervasive in this region, our specific goal is to investigate what the public knows and believes about one of the key concepts, ecosystem services, and identify who they trust to inform them about ecosystem services. This study confirms previous evidence that the public trusts scientists, but they do not always understand the language of science.